2020
DOI: 10.3390/v12090908
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Conjugating Enzyme E2 E Inhibits the Accumulation of Rice Stripe Virus in Laodelphax striatellus (Fallén)

Abstract: The ubiquitin–proteasome system (UPS) is an essential protagonist in host–pathogen interactions. Among the three classes of enzymes in the UPS, ubiquitin-conjugating enzyme E2 plays a dual role in viral pathogenesis; however, the role of insect E2s in interactions with plant viruses is unclear. Twenty E2-encoding genes in Laodelphax striatellus, the small brown planthopper, were identified and classified into 17 groups by transcriptomic and phylogenetic analysis. Full-length cDNAs of four LstrE2s (LstrE2 A/E/G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Besides endonuclease and polymerase activity within tenuivirus RdRps, the RSV RdRp furthermore contains deubiquitination activity [ 79 ]. The biological significance of this activity for the virus infection cycle is unknown, although a recent study has shown that the accumulation of RSV in the planthopper is inhibited by ubiquitin-conjugating enzyme E2 [ 80 ].…”
Section: Virion Composition Genome Organization and Intracellular Replication Cyclementioning
confidence: 99%
“…Besides endonuclease and polymerase activity within tenuivirus RdRps, the RSV RdRp furthermore contains deubiquitination activity [ 79 ]. The biological significance of this activity for the virus infection cycle is unknown, although a recent study has shown that the accumulation of RSV in the planthopper is inhibited by ubiquitin-conjugating enzyme E2 [ 80 ].…”
Section: Virion Composition Genome Organization and Intracellular Replication Cyclementioning
confidence: 99%
“…28 Ubiquitin-conjugating enzyme E2 E could inhibit RSV accumulation in the planthopper body. 29 Conversely, viruses have evolved many strategies to regulate UPS processes mostly by directly interfering with the expression of related genes or by directly interacting with UPS components to maintain appropriate viral protein levels for successful infection. 30,31 The 26S consists of a core particle (CP) and 19S regulatory particles (RPs).…”
Section: Introductionmentioning
confidence: 99%
“…found that UPS regulates the accumulation of Turnip yellow mosaic virus (TYMV) RNA‐dependent RNA polymerase (RdRp) during viral infection and therefore decreases viral replication 28 . Ubiquitin‐conjugating enzyme E2 E could inhibit RSV accumulation in the planthopper body 29 . Conversely, viruses have evolved many strategies to regulate UPS processes mostly by directly interfering with the expression of related genes or by directly interacting with UPS components to maintain appropriate viral protein levels for successful infection 30,31 …”
Section: Introductionmentioning
confidence: 99%
“…For ubiquitin enzymes, E2 contains a ubiquitin-conjugating (UBC) domain, spanning 140-200 amino acids in length, which mediates the interaction between E2 and E3 (Gao et al, 2017). In ubiquitination, E2 plays a key role in regulating the fate and function of target proteins (Li et al, 2020). E2 genes exist as a multigene family that has been identified in model organisms, including Saccharomyces cerevisiae (Seufert et al, 1990), Caenorhabditis elegans (Jones et al, 2002), Homo sapiens (Jiang and Beaudet, 2004), Arabidopsis thaliana (Kraft et al, 2005), and Drosophila melanogaster (Michelle et al, 2009;Nagy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%